2020
DOI: 10.1093/jhps/hnz066
|View full text |Cite
|
Sign up to set email alerts
|

Does pain and hip function improve 2 years after reverse periacetabular osteotomy? A follow-up study of 74 patients

Abstract: Data on outcome in patients with acetabular retroversion (AR) treated with reverse periacetabular osteotomy (reverse PAO) are sparse. The aim of the study was to investigate changes in pain and hip function among patients with AR 2 years after reverse PAO and to examine whether changes in pain were associated with changes in hip function. In addition, to evaluate patient satisfaction and changes in quality of life (QoL). We present a prospective follow-up study with patient-reported outcome data from Aarhus Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Following PAO, we found a total risk of reoperations other than THA of 48%. Removal of osteosynthesis material was most frequent (44%) accounting for 92% of cases, which is higher than reported earlier (6,20). Conversely, we found that the frequency of subsequent hip arthroscopy was 0.4%, which is less than the 11% reported by Larsen et al (6).…”
Section: Reoperationscontrasting
confidence: 72%
“…Following PAO, we found a total risk of reoperations other than THA of 48%. Removal of osteosynthesis material was most frequent (44%) accounting for 92% of cases, which is higher than reported earlier (6,20). Conversely, we found that the frequency of subsequent hip arthroscopy was 0.4%, which is less than the 11% reported by Larsen et al (6).…”
Section: Reoperationscontrasting
confidence: 72%
“…The reverse PAO we describe here includes our technique modifications and differs from the previously described anteverting PAO to treat acetabular retroversion [14,15]. Although PAO to correct acetabular retroversion was originally described as an "anteverting PAO," it has also been described as a "reverse PAO," creating some confusion [1,3,11,16]. The anteverting PAO, as originally described, purely anteverts the retroverted acetabulum, without effort to change the lateral or anterior femoral head coverage [10].…”
Section: Introductionmentioning
confidence: 99%